Analysis of Current Knowledge and Social Implications of Minimal Intervention Prosthodontics: Minimal Intervention Prosthodontics Analysis - Khalil, Uzma; Lohana, Priyanka Chandar; Shafique, Hira; Talpur, Paras; Javed, Farhan; Fatima, Anum (Pakistan Journal of Health Sciences, 2024)
Minimal Intervention Prosthodontics (MIP) focuses on preserving healthy tooth structure while providing functional and aesthetic restorations. Objective: To evaluate the knowledge and social implications of Minimal Intervention Prosthodontics (MIP) among patients at Rehman College of Dentistry, Peshawar, Pakistan. Methods: A cross-sectional survey was conducted on 173 patients aged 35 years and above. Data were collected through a structured questionnaire that assessed patients’ understanding of MIP principles, clinical applications, and perceived social impacts. Statistical analysis was performed to determine associations between knowledge of MIP and demographic factors, such as age, gender, and educational level. Results: Among the respondents, 74% had some awareness of MIP, with higher knowledge levels observed in individuals with advanced education. However, only 41% were familiar with the specific procedures involved in MIP, such as adhesive restorations, sealants and Atraumatic Restorative Treatment (ART). The majority of participants (68%) perceived MIP as beneficial for patient comfort and reducing healthcare costs, though 56% recognized the increased time and expertise required for its application. Additionally, 62% of respondents acknowledged the social benefits of MIP, including preserving natural dentition and improving overall quality of life. Conclusions: The study revealed a moderate level of awareness and understanding of MIP among patients, with educational level significantly influencing knowledge. Despite recognizing its advantages, there was a need for improved patient education to enhance the acceptance and implementation of MIP in dental care